The trend of national and sub-national burden of gastrointestinal and liver diseases in Iran 1990 to 2013; study protocol - Salimzadeh, Hamideh; Ardeshir Larijani, Fatemeh; Abedian, Shifteh; Kalantar Motamedi, Seyed Mohammad; Malekzadeh, Mohammad Masoud; Mohaghegh, Hamid; Sadeghi, Anahita; Sepanlou, Sadaf Ghajarieh; Delavari, Alireza; Saberi-Firoozi, Mehdi; Vahedi, Homayoun; Rezaei Darzi, Ehsan; et al. (Archives of Iranian medicine, 2014)
It is expected that gastrointestinal (GI) and liver diseases inflict considerable burden on health systems in Iran; therefore, highlighting the significance of GI disorders across the other most burdensome diseases requires comprehensive assessment and regular updates of the statistics of such diseases in Iran. To assess in-depth sub-national estimates and trends for the incidence and prevalence of selected GI and liver diseases by age, gender and province over the period 1990 - 2013 in Iran. This is a national and sub-national burden of disease study on 21 GI diseases using all available data sources, including cancer registry, death registration system data, hospital data, and all available published data. Analyses will be performed separately by gender, age groups, year, and province. We will conduct 21 separated systematic reviews of the literature for 21 diseases categories through searching online international electronic databases (i.e. the Medline database of the National Library of Medicine, Web of Science, and Scopus), Iranian search engines (i.e., IranMedex, Scientific Information Database (SID), and IRANDOC), and gray literature. We will search the medical literature published between January 1985 and December 2013. We generated two models, Spatio-temporal and Multilevel Autoregressive models, to estimate mean and uncertainty interval for the parameters of interest by gender, age, year, and province. The models will be informed by data of gender, age, year, and province. Markov Chain Monte Carlo (MCMC) methods will be used to perform Bayesian inference in both modeling framework. All programs will be written in R statistical packages (version 3.0.1). We will calculate and present 1990 to 2013 trends in terms of prevalence, years of life lost due to premature mortality (YLLs), years lived with disability (YLDs), and disability-adjusted life years DALYs for the 21 selected GI diseases by gender, and province. We will also quantify the uncertainty interval for the estimates of interest. Results of the present study will have implications for policy making; as they allow for understanding geographic distributions of the selected GI diseases, and identifying health disparities across provinces.